New Learning Adaptation of the Online-Offline Courses - Adzanil Prima Septy (Rumah Jurnal UIN Bukittinggi, 2022)
Based on the current study, this paper aims to discuss how students managed their new learning adaptation in online-offline learning activities in continuous semesters as their efforts to achieve the learning objectives, namely English Proficiency, according to the general objectives of the course and characteristics. This study explored how students deal with some problems on their online courses independently to meet course objectives. The study reflected how students engaged in learning problems in a shocking moment that occurred in the first quarter of 2020 at the start of the covid-19 pandemic that suddenly moved traditional face-to-face classrooms to multiple online learning systems. This study found that students practiced their strategies in such critical situations to develop their competencies to meet course objectives. This research was qualitative. The students’ responses collected from a series of questionnaires distributed while attending several semi-online courses managed by researchers during the ongoing COVID-19 pandemic at the Bachelor Program of the English Education Department, Bung Hatta University and the Counseling Department of IAIN Batusangkar, semester I academic year 2021/2022 (August 2021-January 2022) were the data of the research. This study has paid a special concern for teaching and learning management in the coming semesters in the midst of the ongoing covid-19 pandemic. This study identified how students adapt to online learning with conditions: (1) the support for the availability of Information and Communication Technology (ICT) facilities in the environment where they live, and (2) the influence of the culture and social characteristics of the place where they liveArtikel ini melaporkan hasil penelitian bagaimana mahasiswa mengelola adaptasi baru pembelajaran dalam konteks kegiatan pembelajaran online-offline secara berkelanjutan dalam kondisi pandemi covid-19 sebagai upaya mereka untuk mencapai tujuan pembelajaran, yaitu Kemahiran Bahasa Inggris, sesuai dengan tujuan dan karakteristik mata kuliah. Artikel ini merangkum seperti apa mahasiswa menghadapi kendala pada perkuliahan daring-luring mereka secara mandiri untuk mencapai tujuan perkuliahan. Pada penelitian ini dicerminkan bagaimana mahasiswa terlibat dalam beradaptasi pembelajaran dalam kondisi pandemi covid-19 yang memindahkan ruang kelas tradisional tatap muka ke beberapa sistem pembelajaran daring yang terjadi sejak kuartal pertama tahun 2020. Dalam penelitian ini juga dilaporkan bahwa mahasiswa menggunakan strategi mereka untuk beradaptasi dalam situasi kritis seperti itu dalam mengembangkan kompetensi sebagaimana tujuan mata kuliah.Penelitian ini bersifat kualitatif. Data penelitian ini berupa tanggapan mahasiswa yang dikumpulkan dari kuesioner yang dibagikan saat mengikuti beberapa mata kuliah semi online yang dikelola oleh peneliti selama pandemi covid-19 yang sedang berlangsung pada Program Sarjana Pendidikan Bahasa Inggris Universitas Bung Hatta dan Konseling IAIN Batusangkar, semester I tahun ajaran 2021/2022 (Agustus 2021-Januari 2022). Kajian ini menjadi perhatian khusus dalam manajemen belajar-mengajar selama semester di tengah pandemi covid-19 yang sedang berlangsung ini. Kajian ini mengidentifikasi bagaimana mahasiswa beradaptasi dengan pembelajaran daring-luring dengan kondisi (1) dukungan ketersediaan sarana Teknologi Informatika Komunikasi (TIK) di lingkungan tempat tinggalnya, dan (2) pengaruh budaya dan karakteristik sosial tempat tinggalnya.